Low‐intensity focused ultrasound, a novel approach to epilepsy treatment in developing countries. Issue 1 (21st December 2022) - Afif, Sadaf; Rehan, Syeda Tayyaba; ul Hussain, Hassan; Islam, Md. Saiful
Abstract: Approximately 80% of patients with epilepsy reside in poor resource settings. Despite the continued advancements and development of new treatment approaches, epilepsy remains a major health problem in developing countries. Consistent findings of epidemiologic studies reflect that both prevalence and treatment gap are higher in the developing world. The objective of this short review was to evaluate current treatment options and low‐intensity, pulsed‐focused ultrasound (FUS) as a potential new treatment option for epilepsy. Although some of the patients could be candidates for surgery, many factors, including poor health‐care infrastructure, socioeconomic status, risks and complications associated with the surgery, and patients' preferences and attitudes toward the surgical procedure, limit the adherence to get surgical therapies. Low‐intensity FUS, a novel and noninvasive therapeutic approach, has the potential to be approved by regulatory bodies and added to the list of standard treatment options for epilepsy. Improved understanding of epilepsy's prevalence and incidence in developing worlds, identification of potential new therapeutic options, and their evaluation through continuous studies and clinical trials are needed to reduce the burden of epilepsy and the treatment gap. Abstract :